2020
DOI: 10.1124/jpet.120.265017
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Mechanisms of Chronic Pain: A Focus on Microglia and P2X4R

Abstract: For over two decades, purinergic signaling in microglia has persisted in the spotlight as a major pathomechanism of chronic pain. Of the many purinoreceptors, the P2X4R of the ionotropic family has a well-described causal role underlying chronic neuropathic pain. This review will first briefly examine microglial P2X4R signaling in the spinal cord as it relates to chronic pain through a historical lens, followed by a more in-depth examination of recent work, which has revealed major sex differences. We also dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 102 publications
2
33
0
Order By: Relevance
“…but not in females 3,10,11 . To study the differences in responses of male and female microglia to peripheral nerve injury, we compared DEGs between two sexes.…”
Section: Peripheral Nerve Injury Induces Profound Sex-specific Changes In the Microglia Transcriptomementioning
confidence: 85%
See 2 more Smart Citations
“…but not in females 3,10,11 . To study the differences in responses of male and female microglia to peripheral nerve injury, we compared DEGs between two sexes.…”
Section: Peripheral Nerve Injury Induces Profound Sex-specific Changes In the Microglia Transcriptomementioning
confidence: 85%
“…Sexual dimorphism of microglia involvement in neuropathic pain has been extensively studied, revealing that microglia are necessary for the development of hypersensitivity in males but not in females 3,10,11 . To study the differences in responses of male and female microglia to peripheral nerve injury, we compared DEGs between two sexes.…”
Section: Peripheral Nerve Injury Induces Profound Sex-specific Changementioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have revealed that the contributing role of microglia in chronic pain is male biased [35,36]. In the spinal cord, activating Toll-like receptor 4, which is primarily expressed by microglia, by the agonist lipopolysaccharide, causes pain behavior in male but not female mice [37].…”
Section: Discussionmentioning
confidence: 99%
“…Sex dimorphism has been reported in some pain mechanisms [71][72][73] . In particular, a recent study reported that neuropathic pain is accompanied by sex-specific changes in the excitability and synaptic function of different subtypes of GABAergic neurons in prelimbic cortex 72 .…”
Section: Prementioning
confidence: 99%